Tales of Dark-skinned Women : Race, Gender and Global Culture. (Taylor & Francis, 1998)
This text looks at the way race and gender are portrayed in popular culture, focusing on the representation of black women. It incorporates a discussion of the politics of representation in Britain and North America and the shift from negative stereotypes to positive images to postmodern knowingness. The author is especially interested in the reach of various race/gender literacies, including the impact of North American racial discourse has had on British conceptions of Asian and Afro-Caribbean femininity.